Critical medical humanities: embracing entanglement, taking risks. Issue 1 (7th June 2015) - Viney, William; Callard, Felicity; Woods, Angela
Abstract : What can the medical humanities achieve? This paper does not seek to define what is meant by the medical humanities, nor to adjudicate the exact disciplinary or interdisciplinary knowledges it should offer, but rather to consider what it might be capable of doing. Exploring the many valences of the word 'critical', we argue here for a critical medical humanities characterised by: (i) a widening of the sites and scales of 'the medical' beyond the primal scene of the clinical encounter; (ii) greater attention not simply to the context and experience of health and illness, but to their constitution at multiple levels; (iii) closer engagement with critical theory, queer and disability studies, activist politics and other allied fields; (iv) recognition that the arts, humanities and social sciences are best viewed not as in service or in opposition to the clinical and life sciences, but as productively entangled with a 'biomedical culture'; and, following on from this, (v) robust commitment to new forms of interdisciplinary and cross-sector collaboration. We go on to introduce the five other articles published in this special issue of the journal, reflecting on the ways in which collaboration and critique are articulated in their analyses of immunology, critical neuroscience, toxicity, global clinical labour, and psychological coercion and workfare. As these articles demonstrate, embracing the complex role of critical collaborator—one based on notions of entanglement, rather than servility or antagonism—will, we suggest, develop the imaginative and creative heterodox qualities and practices which have long been recognised as core strengths of the medical humanities.